Verse Kunst uit de Enschedese ateliers. (Enschede : de Enschedese ateliers, 1994)
Appel, Pieter ; Arendsma, Adrie ; Baake, Frans ; van der Beek, Margreet ; van bergen, Ingrid ; Beute, Carolina ; Blom, Tine ; Bonder, Miriam ; Bos, Seakle ; Bosman, Monique ; Bouwhuis, Marion ; Breg, Piet ; Busschers, Herma ; Celic, Tatjana ; Celic, Zivojin ; Cochius, Elsbeth ; Coelen, Heins Van der ; Douma, C. ; Derks, Gert ; Dubbink, Gonny ; Dijkman, Manje ; Dijkstra, Dia ; Ghazi, Taïb El ; Endt, Erik Van Der ; Engelbarts, Corine ; Eshuis, Anne ; Geerlings, Arnold ; geerts, Peter ; gering, Gert ; Gerritsen, Hans ; Van Gorkum, Jeroen ; Gouriye, Habib ; Grosz, Gabriella ; Haan, Frans ; Hajenius, Paul ; Harmsen, Ton ; Hassink, Dorothea ; Heier, Tjabele ; Hetterscheid, A. ; Hollewand, Tineke ; Holthinrichs, Margot ; Hoogers, Peter ; Hul, Ruud Van 't ; Boom, Suzy Hulshoff-V.d. ; Van Hulst, Veronica ; Janssens, Yempke ; Jarram, Nour-Eddine ; de Jong, Hans Peter ; Jongma, Clemens ; Kamphuis, Henk ; Kamphuis, Ivo ; Kamphuis, Mimi ; Kamphuis, Miranda ; Kamphuis, Sikko ; Kleima-Roorda, Minke ; Wassink, Hanneke Klein ; Klomp, R. ; Brink, Helga Kock am ; Koelman, B. ; Kok, Cisca ; Kok, Erik ; Kok, Nol ; Kratz, S. ; Krikhaar, Eugénie ; Kusber, Vera ; Lammerink, Joel ; Landsman, Loes ; van der Linden, T. ; Lodewijk, Hans ; Van Loon, Mark ; Maassen, Henk ; Malingré ; Malmstrom, Jan ; Meijer, Renée ; Mollee, Yvonne ; Nieuwenhuizen, Hetty v.d. ; Noordaa, Justine Van der ; Nijland, Alette ; Oortwijn, C. ; Otte, Marc ; Otter, Bert ; Nijhuis, Jolande Oude ; Wolbers, Adeline Oude ; Pabon, Ria ; Pisula-Mandziej, Anna ; Radstake, Petra ; Rikhof, Francis ; Ringenier, Dries ; Roesink, Marcel ; Rutjes, Hans ; Schoenmakers, Petra ; Schouman, Merel ; Seinen, Frank ; Siebelt, Ben ; Skuladottir, N. ; Slothouber, Wieger ; Smit, H. ; Sueters, Joyce ; Timmerman, Marijke ; etc.
Speciale kast : groot formaat
boek